The Effects of E-cigarette Smoking, Cigarette Smoking, and Non-smoking on Lung Function, Respiratory Muscle Strength, and Short-term Memory in Undergraduate Student Aged 18-35 Years - Sonpeayung, Rattanaporn; Wibunthiti, Thitiya; Dathaisong, Manatsanan (Journal of health and health management, 2025)
This research was a cross-sectional study aimed to comparison the effects of e-cigarette smoking, cigarette smoking, and non-smoking on lung function, respiratory muscle strength, and short-term memory among undergraduate students aged 18-35 years. A purposive sampling method was employed, with participants divided into three groups: e-cigarette smokers, cigarette smokers, and non-smokers, each consisting of 20 individuals. The participants were assessed for lung function parameters, including forced vital capacity (FVC), forced expiratory volume in one second (FEV1), the FEV1/FVC ratio, and peak expiratory flow rate (PEFR), respiratory muscle strength, assessed by maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP), and short-term memory. Differences between groups were analyzed using one-way ANOVA followed by Bonferroni post hoc analysis, with statistical significance was set at a p-value < .05. The results indicated statistically significant differences in lung function (FEV1, FVC, and PEFR), respiratory muscle strength (MIP and MEP), and short-term memory scores among the three groups (p < .05). Specifically, the e-cigarette and cigarette smoking groups exhibited significantly lower values in FEV1, FVC, PEFR, MIP, MEP, and short-term memory compared to the non-smoking group (p < .05). These findings provide important evidence for the development of strategies aimed at promoting prevention and awareness campaigns regarding the use of e-cigarettes and cigarettes, highlighting the potential long-term health implications of their use.